Central Africa,1878
includes letters from: John Boden Thomson, Kirasa, Mpwapwa [later Dodoma region,Tanzania], Mukonduku (West Ugogu), Uyanguru (Urambo, Tabora region) and Ujiji [later Kigoma region, Tanzania] - wagon transport, expedition; travel with porters; tsetse fly; arrival at Ujiji near shores of Lake Tanganyika with Edward Hore and Walter Hutley Edward Hore, Rudewa, Kirasa, Junnyo [Chunyo], Kwikuru and Ujiji - started with 240 carriers; Arthur Dodgshun, Kirasa, Zanzibar, Bigilo, Mpwapwa, Mawara Ugogu, Kisarusaru (West Ugogu) and Ujiji - willing to settle at Urambo [later Tanzania, Tabora region]; death of John Boden Thomson Walter Hutley, Mukonduku and Ujiji - failure of wagons Elbert Clarke, Zanzibar Boustead, Ridley & Co, Zanzibar Dr J Kirk, Zanzibar